Our Library’s Role in Helping Students Make Sense of Generative AI - Davis, Shelly; Rogers, David (Maine Policy Review, 2024)
The authors of this commentary describe efforts by the library at Husson University in Bangor, Maine, to provide all Husson students with an opportunity to build foundational understandings of generative AI.